2015
DOI: 10.1002/jbm.a.35556
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid use of combined and sequential delivery of growth factors and ultrasound stimulation in porous multilayer composite scaffolds to promote both vascularization and bone formation in bone tissue engineering

Abstract: In this study, a multilayer coating technology would be adopted to prepare a porous composite scaffold and the growth factor release and ultrasound techniques were introduced into bone tissue engineering to finally solve the problems of vascularization and bone formation in the scaffold whilst the designed multilayer composite with gradient degradation characteristics in the space was used to match the new bone growth process better. The results of animal experiments showed that the use of low intensity pulsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…For example, Parmaksiz et al transplanted DBM and DBM containing magnetic particles to bilateral critical-size cranial defects of rats with or without PEMF exposure, and results revealed that exposed groups of DBM and DBM containing magnetic particles show improved bone regeneration and reduced fibrous formation compared with unexposed groups (Parmaksiz et al, 2021). Yan et al also verified that postoperative LIPUS could promote the healing of rabbit femurs defects (Yan et al, 2016). Therefore, postoperative biophysical stimuli loading strategies show great promise in bone tissue engineering, but they remain poorly explored.…”
Section: Postoperative Biophysical Stimuli Loading Strategiesmentioning
confidence: 99%
“…For example, Parmaksiz et al transplanted DBM and DBM containing magnetic particles to bilateral critical-size cranial defects of rats with or without PEMF exposure, and results revealed that exposed groups of DBM and DBM containing magnetic particles show improved bone regeneration and reduced fibrous formation compared with unexposed groups (Parmaksiz et al, 2021). Yan et al also verified that postoperative LIPUS could promote the healing of rabbit femurs defects (Yan et al, 2016). Therefore, postoperative biophysical stimuli loading strategies show great promise in bone tissue engineering, but they remain poorly explored.…”
Section: Postoperative Biophysical Stimuli Loading Strategiesmentioning
confidence: 99%
“…Previous studies have revealed key components of BTE [ 21 , 22 , 23 , 24 , 25 , 26 ]. According to these studies successful bone regeneration relies on the combination of (1) a bioactive scaffold [ 27 , 28 , 29 , 30 , 31 ]; (2) osteoprogenitor cells [ 21 , 26 , 32 , 33 , 34 , 35 ]; (3) growth factors (GF) [ 23 , 36 , 37 , 38 , 39 , 40 ] and (4) adequate vascularization [ 41 , 42 , 43 ] ( Figure 1 ).…”
Section: Recent Developments In Bone Tissue Engineeringmentioning
confidence: 99%
“…Previous studies have revealed key components of BTE [21][22][23][24][25][26]. According to these studies successful bone regeneration relies on the combination of (1) a bioactive scaffold [27][28][29][30][31]; (2) osteoprogenitor cells [21,26,[32][33][34][35]; (3) growth factors (GF) [23,[36][37][38][39][40] and (4) adequate vascularization [41][42][43] (Figure 1). Natural polymers are particularly effective for regenerative medicine application for two main reasons.…”
Section: Recent Developments In Bone Tissue Engineeringmentioning
confidence: 99%
“…In addition, they also found the function of modulating immunity and inducing immune tolerance of allogeneic mesenchymal stromal cells (Peng et al, 2012). Likewise, growth factors such as BMP-2 and TGF-β1 and vascular endothelial growth factor (VEGF) are also introduced to scaffolds to enhance bone repair (Qu et al, 2015;Yan et al, 2016). Yang's group developed PLGA/PCL scaffold modified by silver impregnation, collagen coating, and electrospinning; this scaffold showed osteogenic and antimicrobial properties for orofacial tissue regeneration (Qian et al, 2019).…”
Section: Bonementioning
confidence: 99%